Debates in transgender, queer, and feminist theory: contested sites - Elliot, Patricia (Queer interventions, 2010)
Intersecting the domains of women's studies, sexuality, gender and transgender studies, Debates in Transgender, Queer, and Feminist Theory provides a critical analysis of key texts and theories, engaging in a dialogue with prominent theorists of transgendered identity, embodiment and sexual politics, and intervening in various aspects of a conceptually and politically difficult terrain.
Keywords: LGBTQIA2+; approches et analyses; corps; cours; discipline; identités LGBTQIA2+; lit4700; premier cycle; ressource en ligne; sciences humaines; sociologie; thématiques; transféminisme

From mastery to analysis: Theories of gender in psychoanalytic feminism - Elliot, Patricia (Cornell University Press, 1991)
Critique des approches psychanalytiques en études féministes et de l'hystérie (Kristeva, Irigaray, Chodorow, Dinnerstein, Mitchell, Lacan, Freud) Voir le compte-rendu: Williams, C. L. (1992). [Review of From Mastery to Analysis: Theories of Gender in Psychoanalytic Feminism., by P. Elliot]. Contemporary Sociology, 21(5), 728–729. https://doi.org/10.2307/2075599
Keywords: 1900-1999; corps; cours; discipline; europe; fem1000; france; maternité; premier cycle; psychanalyse; périodes historiques; royaume-uni; régions géographiques; sciences; sciences humaines; sexualité; thématiques